1992
DOI: 10.3109/01480549209035174
|View full text |Cite
|
Sign up to set email alerts
|

BRAZILIN PROTECTS CULTURED RAT HEPATOCYTES FROM BrCCI3-INDUCED TOXICITY

Abstract: Brazilin, the main constituent of Caesalpinia sappan, is an antioxidative substance that has catechol moiety in its chemical structure. Considering the antioxidant-activity of brazilin, it was expected to have protective effects on the toxicities of radical generating chemicals. The incubation of rat hepatocytes with BrCCl3 resulted in significant increase in lipid peroxidation, leakage of cytoplasmic enzymes and cytoplasmic glutathione depletion. The BrCCl3-induced toxicities on hepatocytes were reduced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 12 publications
1
28
0
3
Order By: Relevance
“…Brasilin was originally isolated from C. echinata Lam (Brazil-wood) and C. sappan (sappan-wood). This compound has been reported to have various biological activities including antiinflammatory activity (Hikino et al, 1977), antioxidative activity (Moon et al, 1992), hypoglycemic activity (Kim et al, 1995) and immune function modulating effects Choi and Moon, 1997). Our results clearly show that brasilin is also an antibacterial agent.…”
Section: Discussionsupporting
confidence: 61%
“…Brasilin was originally isolated from C. echinata Lam (Brazil-wood) and C. sappan (sappan-wood). This compound has been reported to have various biological activities including antiinflammatory activity (Hikino et al, 1977), antioxidative activity (Moon et al, 1992), hypoglycemic activity (Kim et al, 1995) and immune function modulating effects Choi and Moon, 1997). Our results clearly show that brasilin is also an antibacterial agent.…”
Section: Discussionsupporting
confidence: 61%
“…Brazilin (in SFN) has been reported to have many biological activities, including immune regulation, 19,20 blood vessel dilatation, 3,11,14 anticoagulation, 8,17 hypoglycemic effect, 10,13,15,16,26,27 oxidative damage inhibition, 6,28 antibiosis, 9 and anti-inflammatory effects. 4,5,7 In addition, it was demonstrated that brazilin powerfully broke deoxynucleic acid chains in anticancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al; [40] Wang et al [22] Hypoglycemic activity Modulation of insulin receptor Lee et al; [41] Kim et al [ [47] Srilakshami et al [21] …”
Section: Cox-2 Inhibitionmentioning
confidence: 99%